Repercussions of melatonin on the risk of breast cancer: A systematic review and meta-analysis - De Arruda Veiga, Eduardo Carvalho; Simões, Ricardo; Valenti, Vitor E. [UNESP]; Cipolla-Neto, Jose; Abreu, Luiz Carlos; Barros, Ernane Pedro Matos; Sorpreso, Isabel Cristina Esposito; Baracat, Maria Candido P.; Baracat, Edmund C.; Soares, Jose Maria (FapUNIFESP (SciELO), 2019)
Breast Cancer is common in women, but its etiology is not yet fully understood. Several factors may contribute to its genesis, such as genetics, lifestyle, and the environment. Melatonin may be involved in the process of breast cancer. Therefore, the aim of this study is to evaluate the influence of the levels of melatonin on breast cancer through a systematic review and meta-analysis. We performed a systematic review according to PRISMA recommendations. The primary databases MEDLINE, Embase, and Cochrane were consulted. There was no restriction on the year of publication and language. Data of systematic reviews from April 2017 to September to 2017 were analyzed. The meta-analysis was conducted using RevMan 5.3 software provided by the Cochrane Collaboration. From a total of 570 articles, 9 manuscripts were included in this review. They analy onzed women with breast cancer and control patients, of which 10% and 90% were in the reproductive period and after menopause, respectively. The lowest level of melatonin was found in approximately 55% of studies with breast cancer in post-menopause. The metanalyses of the studies demonstrated low levels of melatonin in breast cancer patients (n=963) compared with control patients (n= 1332), with a mean difference between the studies of -3.54 (CI -6.01, -1.06). Another difference found was in the comparison between smoking patients, with an average difference between 1.80 [0.97-2.63]. Our data suggest that low levels of melatonin might be a risk factor for breast cancer.
Keywords: Breast Neoplasms; Melatonin; Meta-Analysis; Review; Risk factors